2020
DOI: 10.5488/cmp.23.23801
|View full text |Cite
|
Sign up to set email alerts
|

On the stress overshoot in cluster crystals under shear

Abstract: Using non-equilibrium molecular dynamics simulations we study the yielding behaviour of a model cluster crystal formed by ultrasoft particles under shear. We investigate the evolution of stress as a function of strain for different shear rates, γ, and temperatures. The stress-strain relation displays a pronounced maximum at the yielding point; the height of this maximum, σ p , increases via a power law with an increasing shear range and tends to saturate to a finite value if the limit shear rate goes to zero (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Of course, within a short time this vacancy will be filled up by another particle arriving from another, neighboring lattice site. In our previous work 55 we have demonstrated that cluster crystals exhibit an overshoot in their stress-strain response. For a fixed temperature, the height of this overshoot decreases with a decreasing shear rate.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Of course, within a short time this vacancy will be filled up by another particle arriving from another, neighboring lattice site. In our previous work 55 we have demonstrated that cluster crystals exhibit an overshoot in their stress-strain response. For a fixed temperature, the height of this overshoot decreases with a decreasing shear rate.…”
Section: Introductionmentioning
confidence: 91%
“…Starting our reasoning from Equ. (9) this master curve has thus the form [33,44]: In panel (b) of Fig. 3 we show this master curve onto which the different σ p ( γ)-curves can be mapped.…”
Section: Stress Vs Strain Responsementioning
confidence: 99%
“…The simulation methodology is similar as in previous contributions 18,[21][22][23] . The GEM-4 potential, defined in Eq.…”
Section: B MD Simulations Of the Cluster Crystalmentioning
confidence: 99%